Improving communication skills through online chatting - Hilda Cahyani; Mariana Hoesny (UPT P2M Politeknik Negeri Malang, 2011)
Making the best use of technology has now become a challenge for language teachers. Most language teachers know how difficult it is to get students to use language in class, even more so in a meaningful way, especially at the oral level. Using online chatting can provide learners with opportunities for language interaction since it is within the context that negotiation of meaning and interlanguage development are most likely to occur. Second language acquisition research indicates that negotiation promotes interlanguage development and that learners are most likely to negotiate if opportunities for language interaction are provided. When used strategically with careful planning and focused discussions, chat can be a powerful learning tool which can engage the students with meaningful learning process. Through one-on-one conversations with the instructor, small group work, pairs, individual study of transcripts, and interviews, chat can accommodate difference learning styles. It can be a valuable option to language class, facilitating learning and enhancing communications. Thus, it is essential that language courses use online chat which can bring students to extend the learning process well beyond the traditional classroom approach, since it leads to effective communication tool that fosters a fascinating, authentic and enriching learning experience. The paper is elaborating how to set up online chatting activities in the learning of English as a foreign language. It also describes the strengths of this approach from a pedagogical point of view.